AKUNTABILITAS PELAKSANAAN DANA DESA DI DESA NGLURUP KECAMATAN SAMPUNG KABUPATEN PONOROGO TAHUN 2019 - Rudy Aris Purwanto (Master of Public Administration, Universitas Slamet Riyadi, 2021)
This research is motivated by problems related to the management of village funds.The level of budget absorption and also management which continues to experiencepositive increases from year to year, but in terms of the accountability report, it hasnot carried out village financial administration properly. On the basis of theseproblems, this study aims to analyze and describe the accountability of village fundmanagement in Nglurup Village, Sampung District, Ponorogo Regency in 2019.The accountability theory in this study uses Ellwood in Mardiasmo (2009: 21) thatthe management of village funds must be based on honesty and accountability. law,process accountability, program accountability and policy accountability. Thisstudy uses a descriptive method with a qualitative approach. Research informantsusing purposive sampling technique. Data collection techniques using in-depthinterviews and documentation. The data analysis technique used is interactiveanalysis consisting of data collection, data condensation, data presentation andconclusion drawing. The results showed that the Nglurup Village Government inmanaging village funds had shown accountability, both from the dimensions ofhonesty and legal accountability, process accountability, program accountabilityand policy accountability.Keywords: Honesty and Legal Accountability, Process Accountability, ProgramAccountability, Policy Accountability